Optimasi Pengembangan Desain Ukiran Daun Pintu Presisi dan Unik Pada Industri Kayu dengan Sentuhan Artistic CAD/CAM - Baju Bawono; Tonny Yuniarto; Paulus Wisnu Anggoro; Wardana Wahyu Dharsono (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2024)
Market competition in the wood processing industry, especially furniture products, door leaves, windows, frames, and interior crafts, is getting tighter. Frames and interior crafts is getting tighter. The need for new breakthroughs in developing uniquely patterned doors leaves us with technology to continue sales in an increasingly tight market. One aspect of producing unique patterned door leaves is Indonesian Batik ornaments using Artistics CAD / CAM technology and CNC Router machines. Using this technology, this community service goal of making door leaves patterned with Indonesian Batik ornaments helps SME entrepreneurs compete with better results. The method applied is the development and explorative manufacture of uniquely patterned door leaves with the application of advanced technology software engineering, artistic technology CAD/CAM, and CNC router machines. Process selection using this technology can save 1440 to 538 minutes or 62.64%. The optimal parameter conditions are A2, B2, C3, D3, E3. The optimal simulation and machining time (TS) is 481.56 minutes, and the optimum TR is 538 minutes. Technology produces quality and precision products at a lower cost, from Rp 1.2 million/m2 to Rp 500,000/m2, reduced by 37.36% from the original.